COVID-19 Pandemic: an opportunity to enhance tobacco control in Indonesia - Astuti, Putu Ayu Swandewi (Universitas Udayana, 2021)
Indonesia has been suffering huge burden from tobacco use with more than two million morbidities and US 45.9 billion macro-economic lost due to tobacco use in 2015.23 With the comorbidity of smoking and COVID-19 pandemic, this is the crucial time for the Indonesia government to improve coordinate responses between ministries and the community on tobacco control and COVID-19 recovery.